2014
DOI: 10.1073/pnas.1303676111
|View full text |Cite
|
Sign up to set email alerts
|

Impaired selectin-dependent leukocyte recruitment induces T-cell exhaustion and prevents chronic allograft vasculopathy and rejection

Abstract: Selectin-selectin ligand interactions mediate the initial steps in leukocyte migration, an integral part of immune responses. Fucosyltransferase-VII (FucT-VII), encoded by Fut7, is essential for biosynthesis of selectin ligands. In an established model of cardiac allograft vasculopathy and chronic rejection, Fut7 −/− recipients exhibited long-term graft survival with minimal vasculopathy compared with WT controls. Graft survival was associated with CD4 T-cell exhaustion in the periphery, characterized by impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Exhausted T cells express a variety of coinhibitory receptors, including PD1, TIM3, LAG3, CTLA4, CD160, and BLTA, that modulate the intracellular signaling responsible for this state (24). Although reversal of T-cell exhaustion may be useful in the treatment of chronic infections and cancers, induction of T-cell exhaustion may promote tolerance to autoantigens and alloantigens (24,25). T-cell exhaustion has recently been shown to play a central role in determining clinical outcome in multiple autoimmune diseases (26), and it has been suggested that targeted induction of exhaustion could benefit patients with an aggressive course of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Exhausted T cells express a variety of coinhibitory receptors, including PD1, TIM3, LAG3, CTLA4, CD160, and BLTA, that modulate the intracellular signaling responsible for this state (24). Although reversal of T-cell exhaustion may be useful in the treatment of chronic infections and cancers, induction of T-cell exhaustion may promote tolerance to autoantigens and alloantigens (24,25). T-cell exhaustion has recently been shown to play a central role in determining clinical outcome in multiple autoimmune diseases (26), and it has been suggested that targeted induction of exhaustion could benefit patients with an aggressive course of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the role of T cell exhaustion in transplantation or autoimmunity is not defined. Recently, Sarraj et al [36] showed that genetic depletion of selectin ligand for leucocyte migration led to impaired T cell function. They focused on CD4…”
Section: Discussionmentioning
confidence: 99%
“…The most direct evidence for T-cell exhaustion in transplantation was provided recently in a model of chronic allograft rejection [36 ▪ ] in which fucosyltransferase-VII–deficient ( Fut7 −/− ) recipients, with impaired selectin-dependent leukocyte recruitment, exhibited long-term graft survival with minimal vasculopathy compared with wild-type controls. Graft survival was associated with CD4 + T-cell exhaustion in the periphery, characterized by impaired effector cytokine production, defective proliferation, increased expression of inhibitory receptors PD-1, Tim-3 and KLRG1, low levels of IL-7Rα on CD4 + T cells and reduced polyfunctional CD4 + memory T cells in the allograft.…”
Section: Evidence For T-cell Exhaustion In Transplantationmentioning
confidence: 99%
“…In situations in which donor tissue mass is relatively constant, adoptive transfer experiments in a single recipient with a heart transplant, T cells with differential ability to migrate to the allograft behaved very differently – T cells that could not migrate to the allograft exhibited features of exhaustion [36 ▪ ]. These data are consistent with a report that chemokine (C–C motif) ligand 5 (CCL5)-deficient (CCL5 −/− ) recipients with impaired T-cell recruitment were unable to clear LCMV infection and CCL5 −/− CD8 + T cells exhibited features of exhaustion [49].…”
Section: Factors Affecting T-cell Exhaustionmentioning
confidence: 99%